Evaluation of autonomic modulation through musical stimulation in musicalized and non-musicalized individuals (Research, Society and Development, 2021)
The objective was to evaluate the autonomic modulation of heart rate in musical stimuli in musicalized (GM) and non-musicalized (GNM) individuals. 96 volunteers were evaluated. Four different songs (M1, M2, M3 and M4) were performed. Data analysis was performed in the time domain using RMSSD (square root of the mean square of the differences between consecutive heart rate variability intervals) and pNN50 (NN50: absolute quantity) indices. (count) of NN intervals that differ by more than 50ms from the previous interval - pNN50: percentage of NN50 in relation to the total amount of NN intervals), and in the frequency domain by low frequency indices - LF (sympathetic activity), high frequency - HF (parasympathetic activity) and LF/HF (sympathetic-vagal balance). Results: GM showed lower parasympathetic activity during exposure to different types of music, regardless of gender (p